Thermodynamic Study abut Interactions of Indomithacin drug on surfactants Micelles Of Tween80 and Sodium Dodecyl - Hataf Raheem Mahdi; Mussa Emran Kadhm (Al-Qadisiyah Journal of Pure Science, 2018)
This study includes adsorption of drug indomethacin on the surfactants of both micells Twin 80 and Sodium Dodecyl Sulfate , which symbolizes his short (SDS), and this study comes within the framework of the global effort to treatment the polution water feom medicines and dyes and organic materials and inorganic contaminated. . This study includes adsorption of drug Indomethacin on the ionic surfactants SDS in a mixture of alcohol and water , as well as adsorption on the surfaces of micelle non-ionic and its example Tween80 The study was conducted using spectroscopy visible radiation - ultraviolet (UV-visible) were identified Isotherm adsorption( S2, S3) and according to classified of Giles was applied both from equation Freundlish and Langmuir was calculated thermodynamic functions Î”G, Î”H, Î”S the study showed that the adsorption o n the surface of the SDS emitter of heat any less adsorption increasing the temperature either adsorption on the surface of micelle the Tween80 is endothermic , where proven results to increase the adsorption increasing the temperature . The study also confirmed that the function of the acidic different effect on both surfaces in the adsorption of drug Indomethacin While increasing adsorption of drug on the surfactant of the Tween80 when the function acidic high pH12 Ëƒ pH7> pH4 while the adsorption of the drug Indomethacin on the surfactant of the SDS increases with decreasing function of acid pH4> pH7> pH12.